2020
DOI: 10.3390/cancers12113186
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features as Prognostic Predictors of Poor Outcome in Papillary Thyroid Carcinoma

Abstract: Papillary thyroid cancer (PTC) has an indolent nature and usually excellent prognosis. Some PTC clinicopathological features may contribute to the development of aggressive metastatic disease. In this work, we want to evaluate PTC clinicopathological features that are presurgical prognostic predictors of patients’ outcomes and find which indicators are more adequate for tailoring surgical procedures and follow-up. We studied a series of 241 PTC patients submitted to surgery. All patients’ files and histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Consistent with those studies, we confirmed that LNM was associated with poor prognosis. Male gender is generally thought to be closely related to recurrence of PTC [9,11,33,34]. Ito et al reported that male gender is a risk factor for lymph node recurrence [35].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with those studies, we confirmed that LNM was associated with poor prognosis. Male gender is generally thought to be closely related to recurrence of PTC [9,11,33,34]. Ito et al reported that male gender is a risk factor for lymph node recurrence [35].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer is the most common endocrine malignancy with a rapidly increasing incidence worldwide [ 27 ]. Although the majority of PTC patients have an excellent prognosis, there are also some patients with recurrence, distant metastasis and even other worse ending, affecting the survival time of patients [ 28 , 29 ]. Therefore, it is particularly important to carry out risk stratification management to optimize the therapy for PTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Papillary thyroid cancer (PTC) is the most common thyroid malignancy and generally carries favorable prognosis (3)(4)(5), whereby low risk PTC patients have excellent outcome with conservative treatment, such as adequate surgery and TSH suppressive therapy (6,7). However, a subset of PTC patients present with aggressive disease and experience recurrence, leading to poor prognosis (8)(9)(10). Therefore, identifying tumors with potentially aggressive behavior and increased likelihood of recurrence is crucial for therapeutic decision-making and appropriate patient management.…”
Section: Introductionmentioning
confidence: 99%